Pelaksanaan Pemungutan Pajak Kendaraan Bermotor Pada Kendaraan Ubah Bentuk Offroad Di Kota Surakarta - Arief Rahmaditya; Wasis Suganda (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
Tax is one of the economic instruments of a country. One of the largest and even very influential incomes in Indonesia is local taxes. With the existence of regional taxes, Regional Governments are encouraged to be creative in finding sources of regional revenue funds that can support regional expenditure financing, one of which is the Motor Vehicle Tax (PKB). One source of revenue from Motor Vehicle Tax (PKB) comes from off-road vehicles which are included in the jeep type. Offroad development in Indonesia is growing as time goes by, but the increasing number of offroad motor vehicle users, there are several owners or drivers of offroad vehicles on the road, it can be seen that offroad motorized vehicles do not have a Motorized Vehicle Number (TNKB) or a Motor Vehicle Registration Certificate (STNK) is not valid. or keep the identity of the vehicle a secret in order to avoid too expensive taxes, because in Indonesia the tax that has a double axle (4x4) tends to be higher when compared to other motorized vehicles. The problem in determining the value of motorized vehicle tax on off-road transformed vehicles is because the Regional Revenue Service does not collaborate with specialist workshops or from the physical check there is not a very thorough check on motorized vehicles by the police in the physical check process of motorized vehicles on vehicles changing form offroad.